73.6k views
0 votes
Solve the equation using the quadratic formula. X^2-9x+3=0

User JasonM
by
6.4k points

1 Answer

6 votes

Answer:

The answer is x=
(9+√(69))/(2), x=
(9-√(69))/(2)

Explanation:

x^2=a

-9x=b

3=c

Plug into formula.

Equation:
(9+-√((-9)^2-4(1)(3)))/(2)

Simplify the equation.

Equation:
(9+-√(81-12))/(2)

Subtract 81 and 12.

Equation:
(9+-√(69))/(2)

Spit into two equations

Equation 1:
(9+√(69))/(2)

Equation 2:
(9-√(69))/(2)

Hope this helps!

User FlyingAura
by
6.6k points